Influence of contact conditions on the onset of micropitting in rolling-sliding contacts pertinent to gear applications - Kadiric,A; Rycerz,P (2016)
Copyright © 2016 American Gear Manufacturers Association. Micropitting is a type of rolling contact fatigue surface damage that occurs in concentrated, rolling-sliding contacts, such as those between gear teeth. In contrast to macropitting, where the damage initiates and progresses on the macro contact level, micropitting damage initiates on the surface asperity level. Despite the fact that it is one of the major modes of gear failure, there are currently no universally accepted design guidelines for prevention of micropitting. This paper attempts to provide further understanding on the tribological conditions that may lead to the onset of micropitting in lubricated, concentrated contacts representative of those occurring between gear teeth. In particular, an attempt is made to establish the effect of slide-roll ratio on the extent of microptting. Experimental results obtained on a triple-disc microptting rig under conditions designed to isolate the effects of slide-roll ratio and specific film thickness are presented. In parallel, the potential effect of sliding on film thickness is studied experimentally using a well-proven optical interferometry technique. The results show that increasing the slide-roll ratio increases the extent of micropitting but that the mechanisms responsible for this are not related to any potential effects of the slide-roll ratio on prevalent film thickness as suggested elsewhere, but rather to the increased number of asperity stress cycles at higher slide-roll ratios.